2014
DOI: 10.1128/aem.02417-14
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobia Indigenous to the Okavango Region in Sub-Saharan Africa: Diversity, Adaptations, and Host Specificity

Abstract: The rhizobial community indigenous to the Okavango region has not yet been characterized. The isolation of indigenous rhizobia can provide a basis for the formulation of a rhizobial inoculant. Moreover, their identification and characterization contribute to the general understanding of species distribution and ecology. Isolates were obtained from nodules of local varieties of the pulses cowpea, Bambara groundnut, peanut, hyacinth bean, and common bean. Ninety-one of them were identified by BOX repetitive elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
80
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 61 publications
7
80
1
1
Order By: Relevance
“…Very often, inoculant strains must compete with populations of indigenous or naturalized rhizobia, frequently not effective, but highly competitive and already adapted to the environment (Streeter, 1994; Al-Falih, 2002; Grönemeyer et al, 2014). It is broadly believed that inoculation responses are more likely to occur when there are less than 10 cells of indigenous or naturalized rhizobia per gram of soil (Thies et al, 1991, Thies et al, 1992, Sanginga et al, 1996, Sessitsch et al, 2002, Okogun and Sanginga, 2003), or when a substantial component of the population is not effective (Brockwell et al, 1995, Osunde et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Very often, inoculant strains must compete with populations of indigenous or naturalized rhizobia, frequently not effective, but highly competitive and already adapted to the environment (Streeter, 1994; Al-Falih, 2002; Grönemeyer et al, 2014). It is broadly believed that inoculation responses are more likely to occur when there are less than 10 cells of indigenous or naturalized rhizobia per gram of soil (Thies et al, 1991, Thies et al, 1992, Sanginga et al, 1996, Sessitsch et al, 2002, Okogun and Sanginga, 2003), or when a substantial component of the population is not effective (Brockwell et al, 1995, Osunde et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous survey on root-nodule symbiotic bacteria (Grönemeyer et al , 2014), populations from nodules of pulses collected in the Kavango region of Namibia were analysed, and pure cultures of Bradyrhizobium characterized. On the basis of multi-locus sequence analysis (MLSA) of concatemers of three protein-coding genes ( glnII-recA-rpoB ) and intergenic spacer (ITS) sequences, our analyses identified several novel lineages within the genus Bradyrhizobium (Grönemeyer et al , 2014). A group of eight strains clustered in one of the novel lineages.…”
mentioning
confidence: 99%
“…Strains 14-3 T , 34 1-1, 34 3-1, 35 3-3 and 35 3-4 originated from cowpea, while three other strains, 37 1-1, 37 2-1 and 1BT 1-1, were isolated from Bambara groundnut nodules, the latter in a trapping experiment from soil. All strains were grouped according to BOX-PCR fingerprints (Grönemeyer et al , 2014, strain 1BT 1-1 not shown). BOX-PCR patterns revealed at least four similar genotypes, with the pattern of strain 37 1-1 being very similar to 37 2-1, and patterns of strains 34 1-1, 35 3-3 and 35 3-4 being almost identical.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As many strains used in inoculant formulations originated from indigenous pools of their country of origin, isolation and characterization to identify local elite strains present a strategy to improve BNF. Studies that focused on the characterization of indigenous rhizobium have revealed them as important sources of inoculant strains that are able to improve nodulation and BNF in grain legumes (Fening and Danso, 2002;Bogino et al, 2006;Ampomah et al, 2008;Grönemeyer et al, 2014). Furthermore, effective native strains, when identified, will serve as an important source of local inoculants to enhance BNF and subsequently yields of target legumes due to inherent adaptability to local conditions.…”
Section: Introductionmentioning
confidence: 99%